Towards more effective and dynamic public management in Mexico - Organisation for Economic Co-operation and Development; ProQuest (Firm) ([Paris] : OECD, 2011)
"This public governance review of Mexico examines the regulatory framework in Mexico, explains how e-government could be used to find new approaches to old challenges, and looks at the challenge of professionalising public servants in Mexico."--Publisher description.
Regulation inside government in Mexico : policies and framework -- Leveraging e-government to find new approaches to old challenges -- The challenges of professionalising public servants in Mexico.
"42 2011 10 1 P"--P. [4] of cover.
Includes bibliographical references.
Summary in English and French.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Public administration -- Mexico; Internet in public administration -- Mexico; Mexico -- Politics and government; Electronic books